Impact of Distributed Generation on Relay Protections of Distribution Grid - Zhou Bin; Ying Liming; Zhu Yonggang; Huang Chao (Institute of Advanced Engineering and Science, 2013)
Distributed Generation (DG) generates electricity from many small distributed energy sources or even customer’s small power plants. It always comes up with the terminal customer power quality management and the technology of energy cascade utilization. DG has lots of characteristics such as one single point of access, being power and being load, two operating mode in a grid or as an island, a great deal of application of power electronic devices, easily influenced by natural environmental factors etc. DG has impacts to the original grid in terms of the grid structure, the direction of power flow, the fault current level when a fault happens, etc and subsequently the relay protection mechanism must be looked into. This paper analyses the impact of accessing the DG on the distributed grid in three cases which are the DG accessing to the end of the distributed feeders, to the middle, and the DG accessing to lines, on relay protections. At the end of the paper it also comes up with improvements in detail. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2674